Scleral Fixation of Posteriorly Dislocated Intraocular Lenses by 23-Gauge Vitrectomy without Anterior Segment Approach - Jeroni Nadal; Bachar Kudsieh; Ricardo P. Casaroli-Marano (Journal of Ophthalmology)
Background. To evaluate visual outcomes, corneal changes, intraocular lens (IOL) stability, and complications after repositioning posteriorly dislocated IOLs and sulcus fixation with polyester sutures. Design. Prospective consecutive case series. Setting. Institut Universitari Barraquer. Participants. 25 eyes of 25 patients with posteriorly dislocated IOL. Methods. The patients underwent 23-gauge vitrectomy via the sulcus to rescue dislocated IOLs and fix them to the scleral wall with a previously looped nonabsorbable polyester suture. Main Outcome Measures. Best corrected visual acuity (BCVA) LogMAR, corneal astigmatism, endothelial cell count, IOL stability, and postoperative complications. Results. Mean follow-up time was 18.8 ± 10.9 months. Mean surgery time was 33 ± 2 minutes. Mean BCVA improved from 0.30 ± 0.48 before surgery to 0.18 ± 0.60 (p=0.015) at 1 month, which persisted to 12 months (0.18 ± 0.60). Neither corneal astigmatism nor endothelial cell count showed alterations 1 year after surgery. Complications included IOL subluxation in 1 eye (4%), vitreous hemorrhage in 2 eyes (8%), transient hypotony in 2 eyes (8%), and cystic macular edema in 1 eye (4%). No patients presented retinal detachment. Conclusion. This surgical technique proved successful in the management of dislocated IOL. Functional results were good and the complications were easily resolved.